(untitled) (Research, Society and Development, 2023)
Introduction: Diseases of the cardiovascular system are one of the main causes of morbidity and mortality today. Diseases such as arrhythmias, acute myocardial infarctions, systemic arterial hypertension cause personal and financial losses, both personally and socially. On the other hand, COVID-19 is related to important systemic impacts on humans, in particular, pathologies of the cardiovascular system. Objective: The objective of this work was to evaluate existing data before and after the COVID-19 pandemic related to the most prevalent diseases of the cardiovascular system. Methodology: Data were collected via the platform of the IT department of the Unified Health System, corresponding to the period from January 2018 to January 2020, for data prior to COVID-19 and from February 2020 to December 2022 for data after. Data were analyzed in relation to the number of hospitalizations and mortality rate from cardiovascular diseases. Results: Regarding the number of hospitalizations of patients with heart failure, arterial hypertension and arrhythmias, there was a decrease in the number of hospitalizations during the pandemic period and an increase in the mortality rate in the pandemic period compared to the period prior to the pandemic. Conclusion: A decrease in hospitalization numbers can be justified by social isolation measures, preventive measures to combat COVID-19 and the increase in the mortality rate can be justified by a decrease in the management of these pathologies on an outpatient basis.